Diagnostic Value of Genotypic Analysis in Primary Cutaneous Lymphomas using Standardized BIOMED-2 Polymerase Chain Reaction Protocols: Experience in Daily Clinical Practice - Daniel López Aventín; Fernando Gallardo; Luis Colomo; Ester Moragón; María Carmen Vela; Xavier Duran Jordà; Beatriz Bellosillo; Ramon M. Pujol (Medical Journals Sweden, 2021)
BIOMED-2 Concerted Action BMH4-CT98-3936 (BIOMED-2) PCR protocols are an important diagnostic tool in the evaluation of cutaneous lymphomas. The aim of this study was to assess the diagnostic value of the genotyping results obtained by these techniques in daily clinical practice. A total of 360 paraffin-embedded skin samples were retrospectively reviewed from 114 cutaneous T-cell lymphomas and 35 cutaneous B-cell lymphomas. A total of 249 biopsies from 180 patients with benign lymphoid infiltrates served as controls. T-cell receptor and immunoglobulin gene rearrangements were assessed using the BIOMED-2 method. A combined T-cell receptor gamma and beta assay approach reliably distinguished cutaneous T-cell lymphomas from benign skin T-cell infiltrates (sensitivity 89.4%; specificity 81.5%). Analysis of complete immunoglobulin heavy chain rearrangements also differentiated cutaneous B-cell lymphomas from benign B-cell infiltrates (sensitivity 85.7%; specificity 82.4%). In conclusion, the full BIOMED-2 protocol is a useful aid combined with clinical, histological and immunophenotypical findings for assessment of lymphoid clonality in skin lymphoid proliferations.